Die Blattvertauschung (Lage 12 und 13) im griechischen Sirachbuch - Böhmisch, Franz (Protokolle zur Bibel, 2005)
The permutation of two quires of 160 lines (stichoi) in Sir 30-36 in the hyparchetyp of the Greek Sirach makes us assume that all quires of this manuscript consisted of exactly 160 lines. This however implicates that the first 1767 secured lines of Greek I of the Goettingen Greek Sirach edition must have been written in this greek manuscript in 11 quires with together 1760 lines. The solution might be found in the stichic anomalies of the greek manuscripts of Sirach (cf. Sinaiticus a, Vaticanus B, 929), in which some double lines (distichoi) (Sir 1:1a-b; 1:2a-b; 1:3a-b; 2:18a-b.c-d; 9:2a-b; 10:11a-b; 13:8a-b; 23:19b-c) are written as one line. The Latin translation from a Greek Vorlage, which is not affected by this permutation and originates from another hyparchetyp, retains indirectly some original passages of the greek text of the grandchild against the mainstream of the greek Sirach tradition (cf. Sir 1:3).